2021
DOI: 10.1001/jamanetworkopen.2021.18537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sudden Cardiac Arrest by Race/Ethnicity Among Residents of Ventura County, California, 2015-2020

Abstract: Key Points Question Are race and ethnicity associated with incidence rates, clinical profiles, and outcomes in individuals experiencing sudden cardiac arrest? Findings In this 5-year cohort study of sudden cardiac arrest in a Southern California community comprising 848 112 individuals, rates of sudden cardiac arrest were similar in the non-Hispanic White, non-Hispanic Black, and Hispanic populations, but lower in the Asian population. Survival outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 38 publications
(86 reference statements)
2
45
0
2
Order By: Relevance
“…The population studied here was young (mean 26.6 to 29.8 years vs. approximately 45 to 63 years at start of follow-up in other studies), 3 , 6 , 15 which explains the low prevalence of ischaemic heart disease, 6 and the low incidence of OHCA. 16 Nevertheless, the settings of the current study, assessing more than one million individuals, allowed for a balanced analysis, preventing overestimation of the effect of ischemic heart disease on OHCA.…”
Section: Discussionmentioning
confidence: 68%
“…The population studied here was young (mean 26.6 to 29.8 years vs. approximately 45 to 63 years at start of follow-up in other studies), 3 , 6 , 15 which explains the low prevalence of ischaemic heart disease, 6 and the low incidence of OHCA. 16 Nevertheless, the settings of the current study, assessing more than one million individuals, allowed for a balanced analysis, preventing overestimation of the effect of ischemic heart disease on OHCA.…”
Section: Discussionmentioning
confidence: 68%
“…Ethnicity-specific differences in baseline clinical profile such as obesity, diabetes and renal disease may also contribute. 7 However, this is the first community-based study to report ethnicity-specific reductions in bystander CPR and shockable rhythms during the pandemic. There could be significant opportunities to improve resuscitation characteristics among Hispanics by targeted awareness and education approaches at the community level.…”
Section: Discussionmentioning
confidence: 93%
“…Individuals with out-of-hospital SCA from Feb. 1, 2015 through Feb. 28, 2022 were identified from the ongoing population-based PRESTO (PREdiction of Sudden Death in MulTi-Ethnic COmmunities) study in Ventura County, CA. 7 In this study, all incident cases of presumed SCA requiring cardiopulmonary resuscitation and/or defibrillation by the county's 2-tiered Emergency Medical Services (EMS) system were prospectively identified and adjudicated by study physicians based on detailed review of the EMS pre-hospital care report, pre-arrest and atarrest medical records, death certificates, and autopsies when available. Adjudicated SCA was defined as a sudden, unexpected pulseless collapse of likely cardiac origin; 8 all cases with an identifiable non-cardiac etiology were excluded, such as trauma, drug overdose, and chronic terminal illness (e.g., malignancy not in remission).…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Enhancements in prediction and prevention are a high priority. Several studies have reported that race and/or ethnicity are associated with burden of OHCA 2 , 3 , 4 , 5 but there has been little information from Europe. In their analysis of 1801 OHCA cases among 1,011,565 total immigrants, Garcia et al 6 provide additional evidence from the Danish Cardiac Arrest Registry that incidence of OHCA differs by race/ethnicity.…”
mentioning
confidence: 99%